Beyond virtuality: from engagement platforms to engagement ecosystems. Issue 6 (4th November 2014) - F. Breidbach, Christoph; Brodie, Roderick; Hollebeek, Linda
Abstract : Purpose: – Understanding the role and implications of information and communication technology (ICT) in service is the key research priority for service science and the management of service quality. The purpose of this paper is to address this priority by providing insights into the role of "engagement platforms" (EPs), physical or virtual customer touch points where actors exchange resources and co-create value. Despite an emerging body of literature that emphasizes the fit between engagement and technology-enabled service contexts, EPs remain ill-defined. Specifically, little is known about the particular types of EPs, their characteristics, and implications for the performance of service ecosystems and managing service quality. Design/methodology/approach: – By drawing on two illustrative case studies, the authors investigate and theorize about the characteristics and dynamics of EPs in virtual/physical contexts, and identify if, how and to what extent configurations of EPs may enhance resource exchange within and across service ecosystems. Findings: – By building on emerging research at the service/engagement interface, the paper introduces the notion of the "engagement ecosystem, " as a configuration of individual, mutually dependent EPs that represent specific interactivity-facilitative loci. The paper explicates the relevance of the model and highlight opportunities for future research in this emerging field of inquiry. Research limitations/implications: – The work addresses the call for research at the intersection of ICT and service science through development and application of the engagement ecosystem concept. The theorizing process draws on two illustrative case studies, and thereby provides a theoretical contribution and foundation for future research in this emerging area. Practical implications: – The authors guide managerial decision-making regarding the implementation, adoption, and utilization of engagement ecosystems. Furthermore, the nature of "engagement" as a bridging concept implies that the work can help managers to operationalize service-centric thinking. Originality/value: – By showing how individual EPs form engagement ecosystems, the paper bridges theory and practice, and offers new insight in the realm of practical application of the S-D logic.